Post – Partition Chaos in Mohan Rakesh’s "The Claim" - Sharma, Prakash (Dhaulagiri Journal of Contemporary Issues, 2024)
This paper attempts to analyze the representation of the Indo-Pak partition violence and the chaos aftermath in fictional works especially focusing on Mohan Rakesh's short story "The claim" using the critical insights of trauma theory. An effort is made to show how Rakesh is different from general fictional writers who just write from single perspective and never try to be realistic in the act of representation. Such writers either use the language of otherness or martyrdom. It means, they either glorify or villainies Hindus or Muslims. In contrast, the writer is nearer to reality in presenting the suffering related to partition violence. This research work reveals how Rakesh does not blame any side but artistically shows the real trauma caused by the event of partition to simple people. He presents all four main characters as victims of the partition event and attempts to expose the chaotic situation in post- partition India. It shows how Rakesh blames the bureaucracy of India for making the situation more traumatic by delaying the task of providing compensation for the victims of the partition. Analyzing the data from the primary text using the critical ideas of trauma theorists especially Gyanendra Pandey about the violence, trauma and representation, this paper discusses about the literary representation of the cultural trauma. It tries to reveal how realistically Rakesh presents the continuity of the chaotic situation in India even after the partition event.